APPLYING SANTORINI STYLE TO ROOFTOP INTERIOR DESIGN - Rafia, Indy (Journal of Language Teaching Lingustics and Literature, 2024)
Interior design is the design of a room to organize a room so that it can meet user needs. The interior does not only include the interior of the room but can also include the garden and rooftop. The rooftop is the top floor of a building which is flat and made of concrete in a modern minimalist style house. Currently, many people are starting to use the rooftops of their homes as areas for relaxing, eating, parties, gardens, and so on. Therefore, it is necessary to design the rooftop interior so that it can fulfill safety and comfort using the Santorini style. This design method is a conceptual approach, which will produce a rooftop design in Santorini style, good lighting and ventilation, as well as the required budget.